Bio-based long carbon chain nylon-polyolefin composite with multi-stage synergistic toughening structure and preparation method thereof

CN122978700APending Publication Date: 2026-10-27WUHAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611228234.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

(1)单一相容剂仅能改善界面结合,无法调控内相结构

Benefits of technology

(1)构建“界面-内相-晶界”三级协同增韧结构,从根本上解决刚韧平衡难题。通过界面-内相协同相容助剂、纳米晶型协同调控剂与超支化聚酯的组合式创新,在尼龙-聚烯烃复合材料中首次实现界面、内相、晶界三个层次的同步调控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978700A_ABST
    Figure CN122978700A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of bio-based long carbon chain nylon-polyolefin composite material with multistage synergistic toughening structure and its preparation method, and the composite material includes: bio-based long carbon chain polyamide 30-65 parts by weight, polyolefin composite matrix 20-60 parts by weight, interface-in-phase synergistic compatibility auxiliary agent 3-15 parts by weight, nano-crystalline synergistic control agent 0.5-4 parts by weight, hyperbranched polyester 0.5-6 parts by weight, and optional functional processing aid 0-3 parts by weight.Dual-function synergistic compatibility system contains interface covalent bonding unit and in-phase crystal state control unit, and the mass ratio of the two is 1:1 to 2:1.The above components are sequentially constructed under the time-sequenced gradient reaction extrusion process, interface flexible covalent bonding layer, in-phase toughness γ crystal form, crystal boundary multi-node physical crosslinking network, form "interface-in-phase-crystal boundary" three-level synergistic toughening structure, so that the composite material has high rigidity, high low-temperature toughness and low density, and is suitable for new energy vehicle lightweight interior and exterior trim and structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive polymer functional composite materials technology, and more specifically, to a bio-based long carbon chain nylon-polyolefin composite material with a multi-level synergistic toughening structure and its preparation method. Background Technology

[0002] The automotive industry has set five comprehensive requirements for component materials: low density, high rigidity, high and low temperature toughness, high dimensional stability, and high bio-based content. Traditional single polymer systems are difficult to meet these stringent requirements simultaneously, and multiphase blending has become a core technological path for upgrading the performance of engineering plastics.

[0003] Polyolefin materials, with their advantages of low density (0.90-0.96 g / cm³), excellent processing flowability, and low cost, occupy more than 60% of the market share in automotive interior and exterior trim materials. However, their non-polar molecular structure results in low cohesive energy density, leading to inherent defects such as high low-temperature brittleness, insufficient rigidity, and low heat distortion temperature. Bio-based long-chain nylons (PA11, PA1010, etc.) use renewable resources such as castor oil as raw materials, and the methylene segment length in the molecular chain is ≥8 units. Compared with traditional short-chain nylons (PA6, PA66), they have lower water absorption, better dimensional stability, and low-temperature toughness. However, bio-based nylons have higher density (1.03-1.05 g / cm³), narrower processing window, and higher cost, and their lightweighting effect is limited when used alone.

[0004] Blending bio-based nylon with polyolefins can theoretically achieve complementary properties of "rigidity-toughness-lightweight," but the two differ significantly in molecular polarity, solubility parameters, and crystallization behavior. Direct blending results in severe phase separation and extremely weak interfacial bonding. Existing technologies mainly suffer from the following drawbacks: (1) A single compatibilizer can only improve interfacial bonding and cannot regulate the internal phase structure. For example, Chinese patent CN112662123A uses PP-g-MAH as a single compatibilizer, which only improves the interfacial bonding strength, but completely ignores the key influence of the hydrogen bond network and crystal morphology of the nylon internal phase on the material's toughness. The notched impact strength at -40℃ is only about 6.2 kJ / m². The PA / PP alloy material disclosed in Chinese patent CN116218208B also uses a single maleic anhydride-grafted polyolefin compatibilizer, which is still prone to brittle fracture at low temperatures.

[0005] (2) Nanofillers are prone to agglomeration and lack synergistic effect with the matrix. Chinese patent CN114213789A uses POE-g-MAH and nano-calcium carbonate to toughen PA6 / PP system, but nano-calcium carbonate has high surface energy and is very easy to agglomerate and form stress concentration points during melt blending. In addition, this patent does not regulate the crystal form of nylon.

[0006] (3) Low proportion of bio-based raw materials. Chinese patent CN116925537A discloses a high-temperature bio-based nylon composite material, in which the amount of bio-based polyamide reaches 30-70 parts, but it is not blended with polyolefin, and the density is as high as 1.08 g / cm³. Chinese patent CN116410590A mainly solves the problem of processing fluidity, but does not involve the composite with polyolefin or the complementary properties.

[0007] (4) The preparation process is crude and cannot achieve the synergistic effect of multiple components in stages. Existing technologies generally adopt one-step extrusion, such as the polyamide / polyolefin composite material disclosed in Chinese patent CN118185299A, which leads to premature reaction of compatibilizer, uneven dispersion of nanofillers, uncontrolled crystallization process of nylon, and large phase domain size (>2μm).

[0008] (5) The contradiction between low-temperature toughness and rigidity is difficult to reconcile. In order to improve low-temperature toughness, existing technologies often add a large amount of elastomer (>20 parts), which leads to a significant decrease in material rigidity and heat resistance. For example, the long-chain polyamide composition disclosed in Chinese patent CN115044201A has an elastomer content of 15-25 parts, but the flexural strength is only about 55 MPa.

[0009] (6) Lack of targeted control over grain boundary regions. Most existing technologies focus on the modification of interfaces and grains themselves, neglecting the role of grain boundaries as key regions for stress concentration and crack propagation, which makes materials prone to intergranular fracture at low temperatures. Summary of the Invention

[0010] The technical problem to be solved by the present invention is to provide a bio-based long carbon chain nylon-polyolefin composite material with a multi-level synergistic toughening structure that has high rigidity, high and low temperature toughness and low density, and a method for preparing the same.

[0011] The technical solution adopted by this invention to solve its technical problem is: to construct a bio-based long carbon chain nylon-polyolefin composite material with a multi-level synergistic toughening structure, comprising the following components by weight: Bio-based long-chain polyamide: 30-65 parts; Polyolefin composite matrix: 20-60 parts; Interface-internal phase synergistic compatibility agent: 3-15 parts; Nanocrystalline synergistic regulator: 0.5-4 parts; Hyperbranched polyester: 0.5-6 parts; Functional processing aids: 0-3 parts; The interface-internal phase synergistic compatibility agent comprises interface covalent bonding units and internal phase crystallization regulation units, with a mass ratio of 1:1 to 2:1. In the composite material, the interface covalent bonding units form a flexible covalent bonding layer at the interface between the polyolefin and nylon phases, the internal phase crystallization regulation units promote the formation of γ-crystals in the nylon phase, and the hyperbranched polyester constructs a multi-node physical crosslinking network in the interface and grain boundary regions. Together with the nanocrystalline synergistic regulator, these three components form a three-level synergistic toughening structure of "interface-internal phase-grain boundary".

[0012] According to the above scheme, the bio-based long carbon chain polyamide is a bio-based long carbon chain polyamide with ≥10 carbon atoms and ≥8 consecutive methylene segments, and / or a copolyamide system with a total bio-based monomer content of ≥40%.

[0013] According to the above scheme, the polyolefin composite matrix is ​​selected from at least one of high melt index polypropylene, low density polyethylene, polyolefin elastomer, polypropylene-ethylene random copolymer, and metallocene catalyzed polyethylene.

[0014] According to the above scheme, the interface covalent bonding unit is a functionalized elastomer. The elastomer matrix is ​​selected from at least one of SEBS, POE, and EPDM, and the reactive groups grafted on its surface are selected from at least one of maleic anhydride, ethylene oxide methacrylate, and isocyanate, and the degree of functionalization is 0.8-2.5 wt%.

[0015] According to the above scheme, the internal phase crystallization control unit is selected from at least one of lactam compounds, ethylene-vinyl alcohol copolymers, polyvinyl butyral, oligomeric N-methyllactams, and short-chain polyamide oligomers.

[0016] According to the above scheme, the nanocrystalline synergistic regulator is selected from at least one of nano-talc powder, organic modified montmorillonite, modified graphene, and carboxylated carbon nanotubes.

[0017] According to the above scheme, the hyperbranched polyester satisfies the following structural parameters: branching degree ≥ 0.6, molecular ends contain hydroxyl and / or carboxyl groups with a number of end groups ≥ 5, number average molecular weight Mn is 800-3000, and glass transition temperature Tg ≤ 30℃.

[0018] According to the above scheme, the degree of branching of the hyperbranched polyester is 0.6-0.8.

[0019] According to the above scheme, the mass ratio of the interface covalent bonding unit to the internal phase crystallization control unit is 2:1.

[0020] This invention also provides a method for preparing the bio-based long-chain nylon-polyolefin composite material with the multi-level synergistic toughening structure, which employs a twin-screw extruder with an aspect ratio (L / D) ≥ 40 to perform sequential gradient reactive extrusion at a screw speed of 150-250 rpm, and includes the following steps: (1) Pretreatment: Vacuum dry the bio-based long carbon chain polyamide at 100-110℃ for 4-6 hours until the water content is ≤0.05%, and dry the remaining components at 60-85℃ for 2-4 hours; (2) Sequential gradient reactive extrusion, wherein the twin-screw extruder is configured with five functional temperature zones along the material flow direction: Zone 1 is 180-190℃: Polyolefin composite matrix and nanocrystalline synergistic regulator are added to the main feed port for mild pre-melting and initial dispersion; Zone 2 is 190-210℃: further homogenize the polyolefin melt to form a stable nano-dispersion system; The three zones are 210-230℃: Bio-based long-chain polyamide and hyperbranched polyester are added through the first side feed port. They are first premixed through the weak shear conveying element section to form a "polyolefin continuous phase-nylon dispersed phase" premix. Then, interface-internal phase synergistic compatibility agent and functional processing aid are added through the second side feed port. The mixture is then mixed through the strong shear kneading element section to complete the interface covalent bonding and nylon internal phase hydrogen bond reconstruction. Zone 4 is 230-240℃: It is equipped with a vacuum degassing port to remove reaction byproducts and volatile components; Zone 5 is 230-240℃: the melt is homogenized and extruded through a die; (3) Post-processing: The extruded melt is rapidly cooled in a water bath and dried to a moisture content of ≤0.05%, and then pelletized to obtain the target composite material.

[0021] The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure and its preparation method, as described in this invention, have the following beneficial effects: (1) Construct a three-level synergistic toughening structure of “interface-internal phase-grain boundary” to fundamentally solve the problem of rigidity-toughness balance. Through the innovative combination of interface-internal phase synergistic compatibility agent, nanocrystalline synergistic regulator and hyperbranched polyester, the synchronous regulation of the three levels of interface, internal phase and grain boundary is realized for the first time in nylon-polyolefin composite material.

[0022] (2) Grain boundary targeted toughening effect of hyperbranched polyester. This component utilizes its specific structure (branching degree ≥0.6, end groups ≥5, Tg≤30℃) to construct a multi-node physical cross-linking network in the grain boundary region, breaking only the weak hydrogen bonds at the grain boundary without destroying the rigidity of the crystal nucleus.

[0023] (3) The time-sequential gradient reactive extrusion process ensures the synergistic effect of multiple components. By controlling the temperature gradient in five zones and the timing of the feed ports on both sides, the problems of premature reaction of compatibilizer, uneven dispersion of nanofillers, and runaway crystallization process caused by the simultaneous addition of components in one-step extrusion are overcome, and the product performance stability is significantly improved.

[0024] (4) Synergistic improvement of lightweighting and sustainability. The density of composite materials is controlled at 1.02-1.03 g / cm³, while the proportion of bio-based raw materials can reach 35%-50%, which meets the "carbon neutrality" development requirements of the automotive industry. Attached Figure Description

[0025] The present invention will be further described below with reference to the accompanying drawings and embodiments. In the accompanying drawings: Figure 1 This is a schematic diagram of a sequential gradient reactive extrusion process using a twin-screw extruder. Detailed Implementation

[0026] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0027] This invention utilizes a combined innovative approach of "interface-internal phase synergistic compatibility agent + hyperbranched polyester + nanocrystalline synergistic regulator" to construct a three-tiered synergistic toughening structure of "interface-internal phase-grain boundary," fundamentally solving the challenge of balancing rigidity and toughness. Simultaneously, this invention provides a time-sequential gradient reactive extrusion method for preparing the composite material, ensuring the staged synergistic effect of each component.

[0028] This invention provides a bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure, comprising the following components in parts by weight: Bio-based long-chain polyamide: 30-65 parts; Polyolefin composite matrix: 20-60 parts; Interface-internal phase synergistic compatibility agent: 3-15 parts; Nanocrystalline synergistic regulator: 0.5-4 parts; Hyperbranched polyester: 0.5-6 parts; Functional processing aids: 0-3 parts.

[0029] The working principle and technical effect of each component in the above composite material are obtained by the interaction of each component under the specific shear, temperature and time program of the sequential gradient reactive extrusion process described in this invention, and should not be evaluated independently without the process conditions.

[0030] The interface-internal phase synergistic compatibility aid comprises interface covalent bonding units and internal phase crystallization regulation units, with a mass ratio of 1:1 to 2:1, preferably 2:1. This mass ratio range is set based on the following: when the proportion of internal phase crystallization regulation units is too low (<25%), the competitive decoupling ability of the nylon internal phase hydrogen bond network is insufficient, and the γ-phase conversion rate is below 40%; when its proportion is too high (>50%), the interface covalent bonding units are relatively insufficient, the interfacial bonding force decreases, and the tensile strength decreases by more than 10%.

[0031] The interfacial covalent bonding unit is a functionalized elastomer: the elastomer matrix is ​​selected from at least one of SEBS, POE, and EPDM; its surface is grafted with at least one of reactive groups such as maleic anhydride (MAH), ethylene oxide methacrylate (GMA), and isocyanate (-NCO); the degree of functionality is 0.8-2.5 wt%, preferably 1.2-1.8 wt%. This unit forms covalent bonds at the interface between the polyolefin and nylon phases through in-situ chemical reaction, constructing a flexible interfacial layer, effectively alleviating stress concentration caused by modulus mismatch.

[0032] The internal phase crystallinity regulating unit is selected from at least one of the following: lactam compounds (preferably laurolactam or decanolam with 10-12 carbon atoms), ethylene-vinyl alcohol copolymer (EVOH, vinyl alcohol content 35-45%), polyvinyl butyral (PVB, acetal degree 60-80%), or oligomeric N-methyllactam / short-chain polyamide oligomers (number average molecular weight Mn 500-2000). This unit penetrates into the nylon phase, disrupting the original dense hydrogen bond network through competitive hydrogen bonding, and together with the nanocrystalline synergistic regulator, induces the nylon to transform from α-crystalline to γ-crystalline, with the γ-crystalline form accounting for more than 60%, and the grain size refined to the micrometer level.

[0033] The nanocrystalline synergistic regulator is selected from at least one of the following: nano-talc powder (particle size 50-200 nm, aspect ratio ≥20), organically modified montmorillonite (interlayer spacing ≥3 nm), modified graphene (sheet thickness 0.8-1.2 nm, modified by oxidation or amine), or carboxylated carbon nanotubes (diameter 10-30 nm). A preferred combination is organically modified montmorillonite and modified graphene in a mass ratio of 2:1 to 3:1. This component works synergistically with the internal phase crystalline regulation unit to provide heterogeneous nucleation sites, jointly promoting the directional formation and grain refinement of the γ-crystalline form.

[0034] Hyperbranched polyester has a highly branched three-dimensional spherical molecular structure with the following structural parameters: degree of branching ≥ 0.6, preferably 0.6-0.8; numerous hydroxyl (-OH) and / or carboxyl (-COOH) groups at the molecular ends, with ≥ 5 terminal groups, preferably 5-8; number-average molecular weight Mn of 800-3000; and glass transition temperature Tg ≤ 30℃. The preferred dosage is 1-3 parts by weight.

[0035] The core feature that distinguishes this component from existing general-purpose hyperbranched polyesters lies in the specific combination of structural parameters: high branching degree (≥0.6) endows it with a three-dimensional spherical configuration, which can simultaneously anchor multiple sites at the nylon-polyolefin interface and nylon grain boundary regions; low Tg (≤30℃) ensures that it maintains the ability of molecular chain segments to move at low temperatures, playing a role in stress dissipation; the terminal polyhydroxy / carboxyl groups form weak to moderate strength hydrogen bonds (bond energy 20-30kJ / mol) with nylon amide groups, breaking only the weak hydrogen bonds at the grain boundaries without destroying the strong hydrogen bonds within the crystal nucleus, achieving precise control of "crystal nucleus rigidity - grain boundary flexibility". The synergistic effect of the above structural parameters enables this component to construct a multi-node physical cross-linking network at the interface and grain boundary regions, forming a cross-phase energy dissipation path: "polyolefin continuous phase → interface hyperbranched polyester → nylon grain boundary hyperbranched polyester → nylon amorphous region", realizing stress dissipation step by step and significantly improving low-temperature impact toughness.

[0036] The three-level synergistic toughening structure is the core technical feature that distinguishes this invention from existing technologies: First level (interface layer): Interfacial covalent bonding units form a flexible covalent bonding layer at the interface between nylon and polyolefin, providing interfacial chemical bonding force and buffering modulus mismatch; Second level (inner phase layer): The inner phase crystal state regulation unit and the nanocrystalline synergistic regulator synergistically induce the formation of nylon γ crystal form (γ crystal form ratio ≥ 60%). The γ crystal form has higher deformation capacity due to the looser molecular chain stacking. The third level (grain boundary layer): Hyperbranched polyesters construct a multi-node physical cross-linking network in the grain boundary region, dissipating crack propagation energy and inhibiting intergranular fracture.

[0037] The synergistic effect of the three-level structure enables the composite material to significantly improve its notched impact strength at -40°C without sacrificing tensile and flexural strength.

[0038] The functional processing aids are selected from at least one of antioxidants, heat stabilizers, lubricants, colorants, and flame retardants, with a total amount of 0.3-3.0 parts by weight, and meet the requirements of RoHS / REACH regulations. The total components of the composite material of the present invention meet the ratio of 100 parts by weight.

[0039] like Figure 1 As shown, the present invention also provides a method for preparing the above-mentioned composite material, which employs a time-sequential gradient reactive extrusion process, specifically including the following steps: (1) Pretreatment: Dry the bio-based long carbon chain polyamide in a vacuum drying oven at 100-110℃ for 4-6 hours to make the water content ≤0.05%; dry the polyolefin composite matrix, interface-internal phase synergistic compatibility agent, nanocrystalline synergistic regulator, hyperbranched polyester and functional processing aids in a forced-air drying oven at 60-85℃ for 2-4 hours.

[0040] (2) Sequential gradient reactive extrusion: A twin-screw extruder with an aspect ratio (L / D) ≥ 40 (preferably 48-60) is used, with a screw speed of 150-250 rpm. The extruder barrel is divided into five functional temperature zones from the feed port to the die. The temperature settings, screw component configurations, and feeding sequence for each zone are as follows: Zone 1 (180-190℃): All polyolefin composite matrix and nanocrystalline synergistic regulator are added to the main feed port. Low-shear positive thread element is used for gentle pre-melting and initial dispersion to prevent nanoparticles from breaking or re-aggregating due to strong shear.

[0041] Zone 2 (190-210℃): The polyolefin melt is further homogenized using medium shear threaded elements, so that the nanoparticles are evenly distributed in the continuous polyolefin phase, forming a stable nano-dispersion system.

[0042] Zone 3 (210-230℃): This zone is the core process section, divided into two parts: front and back. Front section (first side feed port, about 1 / 3 screw length from the main feed port): All dried bio-based long carbon chain polyamide and hyperbranched polyester are added and premixed through a weak shear conveying section (forward screw element) with a length of about 5D (D is the screw diameter) to form a "polyolefin continuous phase - nylon dispersed phase" premix. The nylon has not yet completely melted at this stage to avoid premature thermal degradation. Mid-to-late stage (second side feed port, about 1 / 2 screw length from the main feed port): premixed interface-internal phase synergistic compatibility agent and functional processing aid are added and mixed through a strong shear kneading section of about 8D in length (composed of alternating 45° and 90° kneading discs). At this stage, the interface covalent bonding reaction and the reconstruction of hydrogen bonds in the nylon internal phase are completed, promoting the refinement of the dispersed phase (the phase domain size is refined from the micrometer level to 0.2-0.8μm).

[0043] Zone 4 (230-240℃): A vacuum degassing port with a vacuum degree of ≥-0.09MPa is set up to remove reaction byproducts (water, oligomers) and volatile components, ensuring that the interfacial reaction and hydrogen bond reconstruction are fully completed.

[0044] Zone 5 / Die (230-240℃): Employs low-shear positive thread elements to homogenize the melt, stabilize melt pressure and temperature, and prepare for extrusion molding.

[0045] (3) Extrusion and post-processing: After the melt is extruded through the die, it is rapidly cooled in a water bath to fix the γ-crystalline structure of nylon, and then dried by hot air circulation until the moisture content is ≤0.05%, and then pelletized to obtain the target composite material particles.

[0046] The significance of the aforementioned sequential feeding technique lies in the following: first, polyolefins and nano-regulators are added to complete pre-melt dispersion; then, nylon and hyperbranched polyester are added for premixing; and finally, a bifunctional compatibility system is added to complete the interfacial reaction. This sequence avoids premature reaction between the compatibility agent and the nylon end groups, which could lead to an excessively large dispersed phase size. It also avoids the hyperbranched polyester from degrading due to prolonged residence time in the high-temperature, high-shear region, ensuring that the functions of each component are performed at the optimal time.

[0047] In the following examples and comparative examples, the amount of each component is in parts by weight, and the total number of parts all meet the ratio of 100 parts by weight.

[0048] Raw material description: Bio-based long-chain polyamide A1: PA1010, 10 carbon atoms, number average molecular weight approximately 20,000 Bio-based long-chain polyamide A2: PA11, with 11 carbon atoms and a number-average molecular weight of approximately 18,000. Interface covalent bonding unit B1: POE-g-MAH, functionalization 1.5 wt%. Interface covalent bonding unit B2: SEBS-g-MAH, functionalization 1.3 wt%. Internal phase crystalline regulation unit C1: laurolactam Internal phase crystallization control unit C2: EVOH, with 40% vinyl alcohol content. Polyolefin composite matrix D1: LDPE, melt index approximately 5 g / 10 min (190℃, 2.16 kg). Polyolefin composite matrix D2: mPE, density 0.92 g / cm³, melt index approximately 3 g / 10 min (190℃, 2.16 kg). Polyolefin composite matrix D3: POE elastomer Polyolefin composite matrix D4:PP-R Nanocrystalline synergistic regulator N1: Organically modified montmorillonite (OMMT), interlayer spacing 3.2 nm Nanocrystalline synergistic regulator N2: Oxidation-modified graphene (GO), with sheet thickness approximately 1.0 nm. Hyperbranched polyester H1: branching degree 0.7, number of terminal hydroxyl groups 6, number average molecular weight Mn=1500, Tg≈-5℃ (self-made, see preparation example 1 for synthesis method) Hyperbranched polyester H2: Commercially available general-purpose hyperbranched polyester with a branching degree of approximately 0.5, approximately 4 terminal hydroxyl groups, and a number-average molecular weight Mn=2500 (used for Comparative Example 2). Functional processing aid F: Antioxidant 1010 / 168 = 1:2 (0.2 parts) + Calcium stearate (0.15 parts) + Lubricant EBS (0.5 parts) = 0.85 parts Preparation Example 1 (Synthesis of Hyperbranched Polyester H1) Synthesis of G3.0 generation terminal carboxyl hyperbranched polyester with oxalic acid as the core and L-aspartic acid as the branching unit: Step 1: Activation of the G0 generation core S1. Add 100 mL of anhydrous DMF to a 250 mL reaction flask, dissolve 9.00 g (0.1 mol) of oxalic acid in it, and maintain the pressure inside the flask at 1.5 atm under ice bath (0°C) and nitrogen protection. Add a slight excess of 27.36 g of thionyl chloride (SOCl2), slowly raise the temperature to room temperature, and react for 4 hours with a stirring speed of 150 r / min to prepare oxaloyl chloride. After the reaction is complete, remove excess SOCl2 and solvent by vacuum distillation. After drying the obtained oxaloyl chloride, dissolve it in 100 mL of anhydrous DMF solution and store it at 0°C for use as a reaction solution.

[0049] Step 2: Synthesis of G1.0 generation polymer S2. In another 2000mL reaction flask, 61.6g (0.22mol) of L-aspartic acid di-tert-butyl hydrochloride was dissolved in 843.5mL of a mixed solvent of DMF and DCM (volume ratio 1:3), and about 25.3g (about 0.25mol) of triethylamine (TEA) was added as an acid-binding agent.

[0050] S3. Slowly add the DMF reaction solution containing 0.01 mol oxaloyl chloride to the above solution at 0°C. After the addition is complete, heat the reaction system in a water bath to slowly raise the temperature to room temperature and react for 24 hours.

[0051] S4. Post-treatment and purification: The reaction solution was washed sequentially with dilute hydrochloric acid, saturated sodium bicarbonate solution, and saturated brine (dilute hydrochloric acid was mainly used to remove alkaline impurities, saturated sodium bicarbonate solution was used to remove acidic impurities, and saturated brine was used to remove moisture). The organic phase was dried with anhydrous sodium sulfate. After filtration and concentration, the solution was purified by chromatography to obtain G1.0 generation dendritic molecules with tert-butyl ester protected at the end.

[0052] Deprotection of S5 and G1.0 generation hyperbranched polyesters: ① The purified G1.0 generation dendritic molecules (approximately 32.00 g) were dissolved in 480 mL of dichloromethane (DCM), and 256 mL of trifluoroacetic acid (TFA) was slowly added under ice bath conditions. ② The mixture was stirred at 25 °C for 6 hours, and the consumption of the raw material was monitored by HPLC until the raw material peak completely disappeared. ③ The solvent and excess TFA were removed by vacuum evaporation. The mixture was precipitated and washed three times with a methanol and diethyl ether (volume ratio 1:10) system. After vacuum drying, G1.0 generation hyperbranched polyesters with carboxyl groups at the ends were obtained. This polymer has four terminal carboxyl groups, and the yield was 78%.

[0053] Step 3: Synthesis of G2.0 and higher generation polymers S6. Dissolve 0.1 mol of the prepared G1.0 generation hyperbranched polyester in 960 mL of anhydrous DMF (the mass-volume ratio of G1.0 generation hyperbranched polyester to anhydrous DMF is 1 g: 30 mL), and add 0.88 mol EDC·HCl and 1.056 mol DMAP (the molar ratio of EDC·HCl to DMAP is approximately 1:1.2).

[0054] S7. At 0℃, 117.6 g (0.42 mol) of L-aspartic acid di-tert-butyl hydrochloride was dissolved in a mixed solvent of amide and haloalkanes (DMF:DCM = 1:3, volume ratio) and slowly added dropwise to the above activation system over 4 hours. After the addition was complete, the temperature was raised to 25℃ and the reaction was carried out for 36 hours (the reaction time for G2 generation was extended by approximately 50% compared to G1 generation).

[0055] S8, subsequent reactions, post-treatment, and purification steps were similar to the synthesis of G1.0 generation hyperbranched polyesters. During deprotection, the amounts of deprotecting agent (TFA) and organic solvent (DCM) were doubled with each generation. G2.0 generation hyperbranched polyesters with eight terminal carboxyl groups were obtained in 72% yield.

[0056] Step 4: Synthesis of G3.0 generation carboxyl-terminated hyperbranched polyester S9. Using G2.0 generation hyperbranched polyester as the starting material, following steps S6 to S8, a coupling reaction (the reaction time is extended by 30% to 50% based on the G2 generation, and the amount of solvent is doubled according to the generation) and deprotection treatment are carried out to obtain G3.0 generation carboxyl-terminated hyperbranched polyester with 16 terminal carboxyl groups, with a yield of approximately 65%.

[0057] Preparation process conditions: A twin-screw extruder with an L / D ratio of 48 is used, with a screw speed of 180 rpm. The temperature zones are set as follows: Zone 1 185℃, Zone 2 200℃, Zone 3 220℃, Zone 4 235℃, and Zone 5 235℃. The feed inlet on the first side of Zone 3 is approximately 1 / 3 of the screw length from the main feed inlet (the weak shear conveying section is approximately 5D in length, with a forward screw element). The feed inlet on the second side of Zone 3 is approximately 1 / 2 of the screw length from the main feed inlet (the strong shear kneading section is approximately 8D in length, with alternating 45° and 90° kneading discs). The vacuum degree in Zone 4 is ≥-0.09MPa. The cooling method is rapid water bath cooling, followed by hot air drying at 45℃ until the moisture content is ≤0.05%.

[0058] Test method: Tensile strength was tested according to GB / T 1040-2018; flexural strength was tested according to GB / T 9341-2008; notched impact strength of simply supported beams was tested according to GB / T 1043.1-2008 (low-temperature impact was carried out at -40℃); density was tested according to GB / T 1033.1-2008; γ crystal content was determined by wide-angle X-ray diffraction (WAXD), and calculated by peak fitting of characteristic diffraction peaks of α and γ crystal forms; grain size was determined by observing the brittle fracture surface with scanning electron microscopy (SEM) and then calculating the average grain size.

[0059] Example 1 Weigh each component according to the formulation in Table 1. Dry the bio-based long-chain polyamides A1 (PA1010) and A2 (PA11) under vacuum at 105℃ for 5 hours (moisture content ≤0.05%). Dry the polyolefin composite matrix D1, D2, D3, interfacial covalent bonding unit B1, internal phase crystallization control unit C1, nanocrystalline synergistic regulators N1 and N2, hyperbranched polyester H1, and functional processing aid F respectively under forced-air drying at 75℃ for 3 hours.

[0060] In a twin-screw extruder with an L / D ratio of 48, polyolefin composite matrices D1-D3 and nanocrystalline synergistic regulators N1 and N2 were added through the main feed port in zone one; bio-based long-chain polyamides A1 and A2 and hyperbranched polyester H1 were added through the first side feed port in zone three; and interfacial covalent bonding unit B1, internal phase crystallinity regulating unit C1, and functional processing aid F were added through the second side feed port in zone three. After extrusion, the mixture was rapidly cooled in a water bath, dried with hot air at 45°C, and then pelletized to obtain the composite material of Example 1.

[0061] Example 2 The operation is the same as in Example 1, except that B1 and C1 are mixed in a mass ratio of 2:1 (i.e., B1 = 4 parts, C1 = 2 parts), and the remaining components and their proportions are the same as in Example 1.

[0062] Example 3 The procedure is the same as in Example 1, except that the amount of hyperbranched polyester H1 is increased to 3 parts, while the other components and their parts are the same as in Example 1.

[0063] Example 4 The operation is the same as in Example 2, except that B2 (SEBS-g-MAH, functionalization 1.3 wt%) and C2 (EVOH, vinyl alcohol content 40%) are used to replace B1 and C1 respectively, and the remaining components and proportions are the same as in Example 2.

[0064] Comparative Example 1 Using the existing single compatibilizer scheme, with B1=6 parts, without using the internal phase crystal state control unit C1, nanocrystalline synergistic control agent and hyperbranched polyester, the remaining components and parts are the same as in Example 1.

[0065] Comparative Example 2 The operation is the same as in Example 1, except that commercially available general hyperbranched polyester H2 (branching degree about 0.5, terminal hydroxyl group about 4, Mn=2500) is used instead of the self-made hyperbranched polyester H1 of this invention, and the other components and proportions are the same as in Example 1.

[0066] Comparative Example 3 The procedure is the same as in Example 2, except that hyperbranched polyester H1 is not added to examine the effect of the absence of the "grain boundary layer" in the three-level synergistic toughening structure on the performance. The other components and proportions are the same as in Example 2.

[0067] Table 1. Formulations (parts by weight) of Examples 1-4 and Comparative Examples 1-3

[0068] Table 2 Performance Test Results

[0069] Results analysis: (1) Overall effect of the three-level synergistic toughening structure (Example 1 vs. Comparative Example 1) Example 1, employing a complete scheme of bifunctional compatibility system + nano-regulator + self-made HBP, achieved an impact strength of 12 kJ / m² at -40℃, while Comparative Example 1, using only a single interfacial covalently bonded unit, only achieved 5 kJ / m², representing a 140% improvement. Simultaneously, the γ-crystalline content in Example 1 increased from 25% to 62%, and the grain size was refined from 1.8 μm to 0.4 μm. This indicates that the three-level synergistic structure of "interface-internal phase-grain boundary" is synchronously regulated at multiple levels, which is the fundamental reason for the improved low-temperature toughness.

[0070] (2) Effect of mass ratio optimization of compatible system (Example 2 vs. Example 1) Example 2 adjusted the mass ratio of interfacial covalent bonding units to internal phase crystallization control units to 2:1, further increasing the impact strength at -40℃ to 14 kJ / m², while maintaining the tensile strength at 53 MPa. This indicates that the interfacial bonding force and the transformation of the internal phase γ crystal form achieved an optimal balance at this ratio. Example 4 used different material combinations (B2+C2), also obtaining excellent comprehensive performance at a 2:1 ratio, proving that this ratio is universally applicable to different material combinations.

[0071] (3) Grain boundary toughening effect of hyperbranched polyester (Example 1 vs. Comparative Example 2 vs. Comparative Example 3) Example 1 used a self-made hyperbranched polyester H1 (branching degree 0.7, end groups 6, Tg = -5℃), with an impact strength of 12 kJ / m² at -40℃; Comparative Example 2 used a commercially available general-purpose hyperbranched polyester H2 (branching degree approximately 0.5, end groups approximately 4), with the impact strength at -40℃ reduced to 8 kJ / m², a decrease of 33%; Comparative Example 3 contained no hyperbranched polyester, and its impact strength at -40℃ was only 8 kJ / m². This comparison shows that the hyperbranched polyester with specific structural parameters of this invention (high branching degree + multiple end groups + low Tg) is key to achieving grain boundary toughening, and not any hyperbranched polyester can be equivalently substituted. Specifically, high branching degree ensures a three-dimensional spherical configuration and multiple anchoring points, multiple end groups provide sufficient physical crosslinking nodes, and low Tg ensures the mobility of molecular chain segments at low temperatures.

[0072] (4) Optimization of hyperbranched polyester dosage (Example 3 vs. Example 1) In Example 3, increasing the amount of hyperbranched polyester from 2 parts to 3 parts further improved the impact strength at -40°C to 18 kJ / m² (an increase of 50%), while the flexural strength decreased slightly from 78 MPa to 73 MPa (a decrease of 6.4%). These results show that appropriately increasing the amount of hyperbranched polyester can further optimize low-temperature toughness with limited impact on rigidity; 3 parts is the preferred amount in this system.

[0073] (5) Positive correlation between γ crystal content and low-temperature toughness Comparing the γ-crystalline content and -40℃ impact strength data of all examples and comparative examples, a significant positive correlation is observed. Example 3 (68%), with the highest γ-crystalline content, corresponds to the highest -40℃ impact strength (18 kJ / m²), while Comparative Example 1 (25%), with the lowest γ-crystalline content, corresponds to the lowest low-temperature impact strength (5 kJ / m²). This trend verifies the toughening mechanism of this invention, which induces the directional generation of γ-crystalline forms through internal phase crystallization control units and nanocrystalline synergistic regulators.

[0074] Based on the above analysis, the present invention has the following advantages: (1) A three-level synergistic toughening structure of “interface-internal phase-grain boundary” is constructed to fundamentally solve the problem of rigidity-toughness balance. Through the innovative combination of interface-internal phase synergistic compatibility agent, nanocrystalline synergistic regulator and hyperbranched polyester, the simultaneous regulation of the interface, internal phase and grain boundary at three levels is achieved for the first time in nylon-polyolefin composite materials. The impact strength of Comparative Example 1 (containing only 6 parts of single interface covalent bonding unit, without internal phase crystal regulation unit, nano-regulator and hyperbranched polyester) at -40℃ is only 5kJ / m², while that of Examples 1-3 can reach 12-18kJ / m², and the low temperature toughness is significantly improved.

[0075] (2) Grain boundary targeted toughening effect of hyperbranched polyester. This component utilizes its specific structure (branching degree ≥ 0.6, end groups ≥ 5, Tg ≤ 30℃) to construct a multi-node physical cross-linking network in the grain boundary region, breaking only the weak hydrogen bonds at the grain boundary without destroying the rigidity of the crystal nucleus. The impact strength of Example 3 (3 parts of hyperbranched polyester) at -40℃ reached 18kJ / m², while the flexural strength remained at 73MPa.

[0076] (3) The mass ratio optimization of the bifunctional compatible system achieves synergistic effect between the interface and the internal phase. When the interface covalent bonding unit and the internal phase crystal state control unit are matched in a 2:1 ratio (Example 2), the combined impact strength and tensile strength at -40℃ are optimal, indicating that the interface bonding force and the internal phase γ crystal form transformation reach the best balance under this ratio.

[0077] (4) The time-sequential gradient reactive extrusion process ensures the synergistic effect of multiple components. By controlling the temperature gradient in five zones and the timing of the feed ports on both sides, the problems of premature reaction of compatibilizer, uneven dispersion of nanofillers, and runaway crystallization process caused by the simultaneous addition of components in one-step extrusion are overcome, and the product performance stability is significantly improved.

[0078] (5) Synergistic improvement of lightweighting and sustainability. The density of composite materials is controlled at 1.02-1.03 g / cm³, while the proportion of bio-based raw materials can reach 35%-50%, which meets the "carbon neutrality" development requirements of the automotive industry.

[0079] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims. All of these forms are within the protection scope of the present invention.

Claims

1. A bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure, characterized in that, Includes the following components by weight: Bio-based long-chain polyamide: 30-65 parts; Polyolefin composite matrix: 20-60 parts; Interface-internal phase synergistic compatibility agent: 3-15 parts; Nanocrystalline synergistic regulator: 0.5-4 parts; Hyperbranched polyester: 0.5-6 parts; Functional processing aids: 0-3 parts; The interface-internal phase synergistic compatibility agent comprises an interface covalent bonding unit and an internal phase crystallization regulation unit, with a mass ratio of 1:1 to 2:

1. In the composite material, the interface covalent bonding unit forms a flexible covalent bonding layer at the interface between the polyolefin and nylon phases, the internal phase crystallization regulation unit promotes the formation of γ-crystals in the nylon phase, and the hyperbranched polyester constructs a multi-node physical crosslinking network in the interface and grain boundary regions. Together with the nanocrystalline synergistic regulator, these three components form a three-level synergistic toughening structure of "interface-internal phase-grain boundary".

2. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The bio-based long-chain polyamide is a bio-based long-chain polyamide with ≥10 carbon atoms and ≥8 consecutive methylene segments, and / or a copolyamide system with a total bio-based monomer content of ≥40%.

3. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The polyolefin composite matrix is ​​selected from at least one of high melt index polypropylene, low density polyethylene, polyolefin elastomer, polypropylene-ethylene random copolymer, and metallocene-catalyzed polyethylene.

4. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The interface covalent bonding unit is a functionalized elastomer. The elastomer matrix is ​​selected from at least one of SEBS, POE, and EPDM, and the reactive groups grafted on its surface are selected from at least one of maleic anhydride, ethylene oxide methacrylate, and isocyanate, and the degree of functionalization is 0.8-2.5 wt%.

5. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The internal phase crystallization control unit is selected from at least one of lactam compounds, ethylene-vinyl alcohol copolymers, polyvinyl butyral, oligomeric N-methyllactams, and short-chain polyamide oligomers.

6. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The nanocrystalline synergistic regulator is selected from at least one of nano-talc, organically modified montmorillonite, modified graphene, and carboxylated carbon nanotubes.

7. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The hyperbranched polyester satisfies the following structural parameters: degree of branching ≥ 0.6, molecular ends containing hydroxyl and / or carboxyl groups with a number of end groups ≥ 5, number average molecular weight Mn of 800-3000, and glass transition temperature Tg ≤ 30℃.

8. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The degree of branching of the hyperbranched polyester is 0.6-0.

8.

9. The bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure according to claim 1, characterized in that, The mass ratio of the interface covalent bonding unit to the internal phase crystallization control unit is 2:

1.

10. A method for preparing a bio-based long-chain nylon-polyolefin composite material with a multi-level synergistic toughening structure as described in any one of claims 1-9, characterized in that, Sequential gradient reactive extrusion was implemented using a twin-screw extruder with an aspect ratio (L / D) ≥ 40 and a screw speed of 150-250 rpm, including the following steps: (1) Pretreatment: Vacuum dry the bio-based long carbon chain polyamide at 100-110℃ for 4-6 hours until the water content is ≤0.05%, and dry the remaining components at 60-85℃ for 2-4 hours; (2) Sequential gradient reactive extrusion, wherein the twin-screw extruder is configured with five functional temperature zones along the material flow direction: Zone 1 is 180-190℃: Polyolefin composite matrix and nanocrystalline synergistic regulator are added to the main feed port for mild pre-melting and initial dispersion; Zone 2 is 190-210℃: further homogenize the polyolefin melt to form a stable nano-dispersion system; The three zones are 210-230℃: Bio-based long-chain polyamide and hyperbranched polyester are added through the first side feed port. They are first premixed through the weak shear conveying element section to form a "polyolefin continuous phase-nylon dispersed phase" premix. Then, interface-internal phase synergistic compatibility agent and functional processing aid are added through the second side feed port. The mixture is then mixed through the strong shear kneading element section to complete the interface covalent bonding and nylon internal phase hydrogen bond reconstruction. Zone 4 is 230-240℃: It is equipped with a vacuum degassing port to remove reaction byproducts and volatile components; Zone 5 is 230-240℃: the melt is homogenized and extruded through a die; (3) Post-processing: The extruded melt is rapidly cooled in a water bath and dried to a moisture content of ≤0.05%, and then pelletized to obtain the target composite material.

Citation Information

Patent Citations

  • POM / PET alloy material and preparation method thereof

    CN112662123A

  • Borate polymer / ionic liquid composite conductive gel and preparation method and application thereof

    CN114213789A

  • High-temperature-resistant high-toughness long-chain polyamide composition

    CN115044201A

  • A PA / PP alloy material and its preparation method and application

    CN116218208B

  • Long-chain nylon composition as well as preparation method and application thereof

    CN116410590A